Bioinformatic perspectives in the neuronal ceroid lipofuscinoses - Kmoch, Stanislav; Stránecký, Viktor; Emes, Richard D; Mitchison, Hannah M (Biochimica et biophysica acta, 2013)
The neuronal ceroid lipofuscinoses (NCLs) are a group of rare genetic diseases characterised clinically by the progressive deterioration of mental, motor and visual functions and histopathologically by the intracellular accumulation of autofluorescent lipopigment - ceroid - in affected tissues. The NCLs are clinically and genetically heterogeneous and more than 14 genetically distinct NCL subtypes have been described to date (CLN1-CLN14) (Haltia and Goebel, 2012 [1]). In this review we will chronologically summarise work which has led over the years to identification of NCL genes, and outline the potential of novel genomic techniques and related bioinformatic approaches for further genetic dissection and diagnosis of NCLs. This article is part of a Special Issue entitled: The Neuronal Ceroid Lipofuscinoses or Batten Disease.
Keywords: Linkage analysis; Neuronal ceroid lipofuscinosis; Membrane Proteins; Neuronal Ceroid-Lipofuscinoses; Humans; mutace; Bioinformatics; Phenotype; lidé; výpočetní biologie; Topology; Computational Biology; fenotyp; Genetic Predisposition to Disease; neuronální ceroidlipofuscinózy; genetická predispozice k nemoci; Next generation sequencing; membránové proteiny; Mutation